Segmentation of Social Media Platforms in Terms of Perceived Benefits: Cluster Analysis on Brand Followers - Bayır, Talha (My University, 2023)
This study was designed to determine clusters of brand followers on social media platforms and a cluster analysis was carried out to obtain information about the functional, social and communication benefits of social media platforms. The population of this research, which was carried out on social media users, consists of 414 people selected by convenience sampling method. The online survey method was used to collect the data. The research model variables were analyzed by two-step cluster analysis and K mean cluster analysis. Then, discriminant and chi-square analysis were performed. Findings indicate that Instagram users in the cluster 1 have the highest perception of benefit, YouTube users in the cluster 3 have a high perception of benefit, and Facebook and Twitter users in the cluster 2 have an average perception of benefit in terms of brand follow-up.
Keywords: Otelcilik; Konaklama; Spor ve Turizm; İletişim; İşletme; İktisat